2023
DOI: 10.1002/path.6174
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ isoform‐specific regulation of podocyte pyroptosis in lupus nephritis‐induced renal injury

Huimei Zou,
Min Chen,
Xiuhong Wang
et al.

Abstract: As an essential factor in the prognosis of systemic lupus erythematosus (SLE), lupus nephritis (LN) can accelerate the rate at which patients with SLE can transition to chronic kidney disease or even end‐stage renal disease. Podocytes now appear to be a possible direct target in LN in addition to being prone to collateral damage from glomerular capillary lesions induces by immune complexes and inflammatory processes. The NLRP3 inflammasome is regulated by CCAAT/enhancer‐binding protein β (C/EBPβ), which is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…CEBPB mRNA expression was significantly elevated in PBMCs from a cohort of 20 SLE patients compared to 20 gender/age-matched healthy controls [38]. Further studies demonstrated that CEBPB expression was also significantly elevated in LN patients and possibly positively associated with disease progression [39,40]. Interestingly, higher-CEBPB SLE patients tend to have a high titer of certain autoAbs (anti-Sm, anti-SNP, or ANA).…”
Section: Cebpb Enhanced Inflammasome Activity In the Pathogenesis Of Lnmentioning
confidence: 96%
See 2 more Smart Citations
“…CEBPB mRNA expression was significantly elevated in PBMCs from a cohort of 20 SLE patients compared to 20 gender/age-matched healthy controls [38]. Further studies demonstrated that CEBPB expression was also significantly elevated in LN patients and possibly positively associated with disease progression [39,40]. Interestingly, higher-CEBPB SLE patients tend to have a high titer of certain autoAbs (anti-Sm, anti-SNP, or ANA).…”
Section: Cebpb Enhanced Inflammasome Activity In the Pathogenesis Of Lnmentioning
confidence: 96%
“…They then demonstrated that lentiviral shRNA-CEBPB mediated CEBPB knockdown in MRL/lpr LN mice reduced renal pathogenesis and improved renal function [42]. LN was similarly improved in MRL/lpr mice treated with the adeno-associated virus of CEBPB shRNA [39,40]. Collectively, studies suggest that three possible mechanisms are linked to the pathological role of CEBPB in LN: (1) CEBPB enhances NLRP3 inflammasome activation because the inhibition of CEBPB expression is associated with decreased NLRP3 levels [42].…”
Section: Cebpb Enhanced Inflammasome Activity In the Pathogenesis Of Lnmentioning
confidence: 99%
See 1 more Smart Citation
“…Among canonical programmed cell death pathways, apoptosis stands out as the predominant type, although it occasionally intersects with others, notably necroptosis and pyroptosis. 92,111,112 Both necroptosis and pyroptosis are inflammation-inducible pathways that feature a loss of plasma integrity and are characterized by a cascade of signals including MLKL and inflammasome activation, respectively. 71 Additionally, in the absence of concrete evidence regarding the occurrence of ferroptosis in LN podocytes, additional findings are needed to conclusively understand podocyte dysfunction in LN.…”
Section: Targeting Podocyte Deathmentioning
confidence: 99%
“…Furthermore, upregulation of the CCAAT/enhancer-binding protein β (C/ EBP-β) isoform was observed in LN patients and MRL/ lpr mice, while the NLRP3 inflammasome is regulated by C/EBP-β, indicating that it may regulate podocyte pyroptosis. 92 The inflammatory factors released by podocyte pyroptosis induce the proliferation of mesangial cells and the extensive secretion of collagen. 93 These converging lines of evidence underscore the central role of podocyte pyroptosis in LN.…”
Section: Pyroptosismentioning
confidence: 99%